Seven-day vonoprazan and low-dose amoxicillin dual therapy as first-line Helicobacter pylori treatment: a multicentre randomised trial in Japan. Issue 6 (8th January 2020) - Suzuki, Sho; Gotoda, Takuji; Kusano, Chika; Ikehara, Hisatomo; Ichijima, Ryoji; Ohyauchi, Motoki; Ito, Hirotaka; Kawamura, Masashi; Ogata, Yohei; Ohtaka, Masahiko; Nakahara, Moriyasu; Kawabe, Koichi
Abstract : Objective: To date, no randomised trials have compared the efficacy of vonoprazan and amoxicillin dual therapy with other standard regimens for Helicobacter pylori treatment. This study aimed to investigate the efficacy of the 7-day vonoprazan and low-dose amoxicillin dual therapy as a first-line H. pylori treatment, and compared this with vonoprazan-based triple therapy. Design: This prospective, randomised clinical trial was performed at seven Japanese institutions. Patients with H. pylori –positive culture test and naive to treatment were randomly assigned in a 1:1 ratio to either VA-dual therapy (vonoprazan 20 mg+amoxicillin 750 mg twice/day) or VAC-triple therapy (vonoprazan 20 mg+amoxicillin 750 mg+clarithromycin 200 mg twice/day) for 7 days, with stratification by age, sex, H. pylori antimicrobial resistance and institution. Eradication success was evaluated by 13 C-urea breath test at least 4 weeks after treatment. Results: Between October 2018 and June 2019, 629 subjects were screened and 335 were randomised. The eradication rates of VA-dual and VAC-triple therapies were 84.5% and 89.2% (p=0.203) by intention-to-treat analysis, respectively, and 87.1% and 90.2% (p=0.372) by per-protocol analysis, respectively. VA-dual was non-inferior to VAC-triple in the per-protocol analysis. The eradication rates in strains resistant to clarithromycin for VA-dual were significantly higher than those for VAC-triple (92.3% vs 76.2%; p=0.048). The incidence of adverse events was equal between groups. Conclusion: The 7-day vonoprazan and low-dose amoxicillin dual therapy provided acceptable H. pylori eradication rates and a similar effect to vonoprazan-based triple therapy in regions with high clarithromycin resistance. Trial registration number: UMIN000034140.